Design, Modeling and Validation of a Tendon-Driven Soft Continuum Robot for Planar Motion Based on Variable Stiffness Structures - Wockenfus, Wilhelm R.; Brandt, Viktor; Weisheit, Linda; Drossel, Welf-Guntram (IEEE robotics and automation letters, 2022)
Robotic structures based on variable stiffness enable high-performance and flexible motion systems that are inherently safe and thus allow safe Human-Robot Collaboration. This letter presents the design of a robotic structure based on variable stiffness. A robotic manipulator is developed using three variable stiff segments based on particle jamming with a backbone architecture and two tendons for an underactuated motion control of the whole structure. By switching the structural stiffness, the manipulator is able to perform complex planar motion with only one pair of tendons, reducing the number of actuators required. A kinematic modeling approach for the calculation of the forward kinematics of this soft continuum structure is presented, and the validation on the real system is explained. The kinematic simulation is performed with a multibody simulation model (MBS) using rigid body elements in combination with rotational springs. The validation of the model is carried out with visual measurements of the real system using defined target shapes. Simulation and experimental results are discussed and compared also with a common constant curvature model. The developed MBS-model demonstrates a promising modeling approach with a position error lower 3% for the calculation of the presented manipulator under gravity.